Redox-neutral and metal-free synthesis of 3-(arylmethyl)chroman-4-ones via visible-light-driven alkene acylarylation - Ding, Yan; Yu, Shengjiao; Ren, Man; Lu, Ji; Fu, Qiang; Zhang, Zhijie; Wang, Qin; Bai, Jun; Hao, Na; Yang, Lin; Wei, Siping; Yi, Dong; et al. (Frontiers in Chemistry, 2022)
A metal- and aldehyde-free visible-light-driven photoredox-neutral alkene acylarylation with readily available cyanoarenes is described. A variety of 3-(arylmethyl)chroman-4-ones (i.e., homoisoflavonoids) and analogs are efficiently synthesized with good functional group tolerance. This mild protocol relies on a phosphoranyl radical-mediated acyl radical-initiated cyclization and selective radical-radical coupling sequence, and is also further highlighted by subsequent derivatization to chromone and 2H-chromene as well as its application in the three-component alkene acylarylation.